Pflanzenökologie - Schulze, Ernst-Detlef 1941-; Beck, Erwin 1937-; Müller-Hohenstein, Klaus 1936- (Spektrum, Akad. Verl., 2002)
Plant ecology, ecophysiology, autecology, synecology, population ecology.
Keywords: Pflanzenökologie; Lehrbuch